1996
DOI: 10.1056/nejm199602013340507
|View full text |Cite
|
Sign up to set email alerts
|

Legalizing Assisted Suicide — Views of Physicians in Oregon

Abstract: Oregon physicians have a more favorable attitude toward legalized physician-assisted suicide, are more willing to participate, and are currently participating in greater numbers than other surveyed groups of physicians in the United States. A sizable minority of physicians in Oregon objects to legalization and participation on moral grounds. Regardless of their attitudes, physicians had a number of reservations about the practical applications of the act.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(113 citation statements)
references
References 20 publications
4
106
0
3
Order By: Relevance
“…As such, determining the prevalence of the WTHD in chronically ill or endstage patients continues to pose a serious challenge [75]. Although numerous studies carried out mainly in the United States [49,[76][77][78], as well as in Holland [58,79], have sought to specify the prevalence of the WTHD, the above-mentioned limitations (especially the lack of conceptual clarity) make it difficult to obtain comparable results [10].…”
Section: Epidemiology Of the Wthd And Instruments For Measuring Itmentioning
confidence: 99%
“…As such, determining the prevalence of the WTHD in chronically ill or endstage patients continues to pose a serious challenge [75]. Although numerous studies carried out mainly in the United States [49,[76][77][78], as well as in Holland [58,79], have sought to specify the prevalence of the WTHD, the above-mentioned limitations (especially the lack of conceptual clarity) make it difficult to obtain comparable results [10].…”
Section: Epidemiology Of the Wthd And Instruments For Measuring Itmentioning
confidence: 99%
“…3 First, the increasing public interest in humane terminal care necessarily requires that medical professionals be more willing to make and act on predictions about the timing of impending death. A physician's prognostic assessment that a patient is "terminally ill" is an essential element, for example, in the withdrawal or withholding of life support from critically ill patients, 4 in proposals regarding physician-assisted suicide, [5][6][7][8] and in qualifying for the Medicare hospice benefit. 9 Second, as the avoidance of futile treatment assumes increasing prominence for reasons of justice, beneficence, or cost containment, [10][11][12] prognostication-which is, after all, the fundamental and essential basis for a determination of "futility"-will increase in importance.…”
mentioning
confidence: 99%
“…10 Lee et al found that 21 percent of Oregon physicians had received a request for physician-assisted suicide in the past year and that 7 percent had written at least one lethal prescription at a patient's request. 11 In Washington State 12 percent of physicians had received requests for physicianassisted suicide and 4 percent had received a request for euthanasia during the preceding year. 12 In both cases 24 percent of requests were granted.…”
Section: Discussionmentioning
confidence: 99%